International Environmental Agreements : an Introduction. - Andresen, Steinar (Routledge research in environmental politics., 2011)
International environmental agreements provide a practical basis for countries to address environmental issues on a global scale. This book explores the workings and outcomes of these agreements, and analyses key questions of why some problems are dealt with successfully and others ignored. By examining fundamental policies and issues in environmental protection this text gives an easily comprehensible introduction to international environmental agreements, and discusses problems in three areas: air, water and on land. It traces the history of agreements in broad thematic areas related to long.